Arctic root‐associated fungal community composition reflects environmental filtering. Issue 3 (February 2014) - Blaalid, Rakel; Davey, Marie L.; Kauserud, Håvard; Carlsen, Tor; Halvorsen, Rune; Høiland, Klaus; Eidesen, Pernille B.
Abstract There is growing evidence that root‐associated fungi have important roles in Arctic ecosystems. Here, we assess the diversity of fungal communities associated with roots of the ectomycorrhizal perennial herb Bistorta vivipara on the Arctic archipelago of Svalbard and investigate whether spatial separation and bioclimatic variation are important structuring factors of fungal community composition. We sampled 160 plants of B. vivipara from 32 localities across Svalbard. DNA was extracted from entire root systems, and 454 pyrosequencing of ITS1 amplicons was used to profile the fungal communities. The fungal communities were predominantly composed of Basidiomycota (55% of reads) and Ascomycota (35%), with the orders Thelephorales (24%), Agaricales (13.8%), Pezizales (12.6%) and Sebacinales (11.3%) accounting for most of the reads. Plants from the same site or region had more similar fungal communities to one another than plants from other sites or regions, and sites clustered together along a weak latitudinal gradient. Furthermore, a decrease in per‐plant OTU richness with increasing latitude was observed. However, no statistically significant spatial autocorrelation between sites was detected, suggesting that environmental filtering, not dispersal limitation, causes the observed patterns. Our analyses suggest that while latitudinal patterns in community composition and richness might reflect bioclimatic influences at global spatial scales, at the smaller spatial scale of the Svalbard archipelago, these changes more likely reflect varied bedrock composition and associated edaphic factors. The need for further studies focusing on identifying those specific bioclimatic and edaphic factors structuring root‐associated fungal community composition at both global and local scales is emphasized.